2018
DOI: 10.1364/ome.8.001569
|View full text |Cite
|
Sign up to set email alerts
|

Nearest-neighbor sp3d5s* tight-binding parameters based on the hybrid quasi-particle self-consistent GW method verified by modeling of type-II superlattices

Abstract: We report the determination of parameters in the nearest-neighbor sp 3 d 5 s * tightbinding (TB) model for nine binary compound semiconductors which consist of Al, Ga, or In and of P, As, or Sb based on the hybrid quasi-particle self-consistent GW (QSGW) calculations. We have used the determination parameters to calculate band structures and related properties of the compounds in the bulk phase relevant to mid-infrared applications and of the type-II (InAs)/(GaSb) superlattices. For the type-II (InAs)/(GaSb) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In the same manner in Ref. 28, we treated the deformation of each layer with classical elasticity and modified the TB parameters using generalized Harrison's d −2 law. 31) Figure 5 shows the calculated band-gap energies against the experimental ones; [19][20][21]32,33) the structures of the (InAs) n (Ga x In 1−x Sb) m T2SLs are listed in Table VI.…”
Section: Results 2: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same manner in Ref. 28, we treated the deformation of each layer with classical elasticity and modified the TB parameters using generalized Harrison's d −2 law. 31) Figure 5 shows the calculated band-gap energies against the experimental ones; [19][20][21]32,33) the structures of the (InAs) n (Ga x In 1−x Sb) m T2SLs are listed in Table VI.…”
Section: Results 2: Applicationsmentioning
confidence: 99%
“…Alloy parameters adjusted commonly or independently intended to be used with our parameters of binary compounds. 27,28) Al x Ga for on-site and spin-orbit terms, and…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that our sp 3 s * tight-binding parameters reproduce the GaBi band structure very accurately around the Γ point, however the high energy conduction bands do not quantitatively match the published band structure, in particular along the Γ to X direction of the Brillouin zone. This is related to the limitation of the sp 3 s * parametrisation as discussed in the previous studies [27,28]. However, for the GaBiAs material which is a direct band-gap material, the fitted sp 3 s * tight-binding parameters provide a very good description of the band structure properties.…”
Section: Qw Geometry Parametersmentioning
confidence: 93%
“…This topical category encompasses two theoretical studies on narrow-gap semiconductors: Chen et al investigated the impact of Bi on band gap bowing in InP 1-x Bi x ternary semiconductors using first-principle calculations [43]. Sawamura et al evaluated the nearest-neighbor sp 3 d 5 s* tight-binding model parameters for nine binary compound semiconductors using the hybrid self-consistent GW (QSGW) method, and concluded that the tight-binding model provides a reliable theoretical framework to guide superlattice design [44].…”
Section: Narrow-gap Semiconductors and Semiconductor Nanostructuresmentioning
confidence: 99%